Effect of adhesive layer compliance on strength of single-lap hybrid bonded-bolted joints. (1st April 2021) - Bodjona, Kobyé; Fielding, Sean; Heidari-Rarani, Mohammad; Lessard, Larry
Abstract: A combination of bonding and bolting can potentially improve the joining efficiency of composite structures. Several researchers have shown that in specific cases, the joint yield and ultimate strength can be improved in this manner compared to the underlying joints separately. However, their results also demonstrate a strong sensitivity to various design parameters. In this study, the effect of adhesive layer compliance is experimentally investigated on the single-lap hybrid bonded-bolted joint strength. It is found that for a bonded joint with a low compliance adhesive, there is no benefit to adding a fastener on the initial (adhesive) failure. For a high compliance adhesive, it is found that the addition of a fastener significantly delays the initial failure. A mechanism is proposed – supported by a numerical model – that explains the observed behaviour.